Effect of Lifestyle Modification and Metformin on Fetuin-A and Transforming Growth Factor-ß (TGF- ß) in Metabolic Syndrome - Melati Silvanni Nasution; Dharma Lindarto (TALENTA Publisher, Universitas Sumatera Utara, 2019)
Fetuin-A is a liver-synthesized protein that is secreted into serum. Transforming growth factor-β (TGF-β) is a polypeptide member of the TGF-β superfamily of cytokines. The purpose of this study is to evaluate the effects of lifestyle modification and metformin on fetuin-A and Transforming Growth Factor-ß (TGF- ß) in metabolic syndrome (MetS). Forty MetS subjects were randomly assigned to treatment with placebo (n=20) or metformin (n=20) in addition to lifestyle modification for 12 weeks. All 40 participants completed the study. After 12 weeks, both groups had significant reductions in weight, body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP) and diastolic blood pressure (DBP) (all p<0.001). The placebo group also had significant improvement in fasting plasma glucose (FPG) and C-reactive protein (CRP) (p<0,001 ; p<0.05 respectively). Weight, BMI, WC, FPG, 2-hour postprandial glucose (2h-PPG), high density lipoprotein cholesterol (HDL-C), triglycerides (TG), fetuin-A and TGF- ß in the metformin group decreased significantly compared to the placebo group. Reduction of plasma fetuin-A was significantly associated with TG in the metformin group. Lifestyle modification and treatment with metformin for 12 weeks improved cardio-metabolic risk factors in MetS and reduced fetuin-A levels.